Toponymies of lesser-used languages in the North: Issues of socio-linguistic conditions among Inuit and Sámi - Müller-Wille, Ludger (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractBoth Inuit and Sámi have experienced the expansion of colonial state systems and immigrant populations from the south into their territories in Arctic Canada and northernmost Europe respectively. These historical processes have resulted, among other socio-economic conditions, in the superposition and often displacement of their aboriginal toponymy by external interests introducing other languages and place names. In the introduction this paper discusses the socio-linguistic conditions of aboriginal languages in Canada and in Europe. Both situations differ with regard to the legal protection of lesser-used, minority or aboriginal languages. In Europe the linguistic rights of minorities or aboriginal peoples are protected under conventions and by laws on the international and national level. In fact, the framework of the European Union has enhanced the position of languages in general. In the Canadian confederation, with English and French as official languages, specific legal provisions for aboriginal languages exist at the provincial and territorial levels. Still, the levels of protection are considerably weaker for these languages. As case studies the socio-linguistic conditions among the Inuit and Sámi are analyzed by focusing on the maintenance and development of their aboriginal toponymy as cultural and linguistic heritage and expression of human environmental relations. The paper explains recent practical efforts by both Inuit and Sámi to counteract the process of linguistic displacement by developing programs to enhance the development of their integral place name systems. Both Inuit and Sámi institutions have established programs to record and document their oral and historical toponymy, using modern technologies to produce maps and gazetteers. These programs are presented and discussed in the light of cultural self-determination and human and linguistic rights. In conclusion, the question is discussed if communities of lesser-used languages are able to maintain the functional space needed for the security of their languages within a multicultural and multilingual context.